Financial expert CEOs, political intervention, and corporate investment decisions: evidence from the anti-corruption campaign. Issue 3 (16th August 2021) - Anderson, Hamish D.; Liao, Jing; Yue, Shuai
Abstract : Purpose: Employing the anti-corruption campaign as an exogenous political shock, this paper examines how political intervention shapes the impact of financial expert CEOs on firm investment decisions. Design/methodology/approach: This paper uses a sample of 2, 808 Chinese firms listed in the Shanghai and Shenzhen Stock Exchanges from 2003 to 2016. Panel data is used for conducting the analysis controlling for firm, industry, and year fixed effects. Findings: The authors found that CEOs with financial expertise are sensitive to political intervention when making investment decisions. First, financial expert CEOs spend more on R&D expenditure in private-owned companies and they are associated with less R&D expenditure in state-owned enterprises (SOEs). Second, financial expert CEOs are associated with higher investment expenditure in general, but they become less likely to invest more in the post-anti-corruption period. The reduction in investment expenditure due to the anti-corruption campaign is more pronounced in SOEs than in private-owned companies. Third, the anti-corruption campaign promotes R&D investment in general, but in SOEs, expert CEOs tend to be less likely to invest more on R&D after the anti-corruption shock. Originality/value: This paper enriches the growing literature on the impact of political intervention and the role of the anti-corruption campaign on corporate behaviour.